Registrar para preservar : a arquitetura religiosa em madeira na cidade de Maringá-PR - Hoffmann, Alessandra Corsato (2015)
This work has as a research subject the remaining religious wooden architecture in the city of Maringá - PR, which are the chapels of St. Boniface (1940), Santa Cruz (1945) and Our Lady Aparecida (1949), which have been built by carpenters owners of a specific constructive technique responsible for setting the initial scenario of territorial occupation of Paraná. The three chapels are declared as cultural heritage of the city and the first two are declared at the state level, but they have not had their inventories held yet. Therefore, the aims of this research include: carry out the inventory of the three chapels based on the guidelines of Integrated Knowledge System and Management, instrument developed by The National Historic and Artistic Heritage Institute, which has a model and unique methodology of documentation and inventory of cultural property that intention is their protection, appreciation and management; and also propose the registration process optimization of such an instrument including a specific model of registration for religious architecture in wood, once there are still many buildings with such characteristics that are protected by law but have not been inventoried. The research starts with approach of the cultural heritage trajectory, from its initial concept to this day, and preservationist policies implemented at international, national, state and municipal levels, in order to understand the asset value of the studied buildings, and the necessary actions for the preservation of such properties. Following it is adopted the methodology proposed by IPHAN, which consists filling forms developed for capturing and organizing information of the inventoried goods, structured into three modules: Knowledge , Management and Register, each one correspond to an approach sphere of cultural equity. Following the forms guidelines it was defined as territorial trimming the state of Paraná, the thematic focus in wooden architecture and as an analytical universe the wooden chapels of Maringá. Therefore, It was held the state of the art concerning the wooden architecture in Paraná, as well as historical, documentary surveys, physical, photographic and interviews, for the appropriate registration of the chapels above. With the inventory holding of the buildings it was possible to verify the historical and architectural value of the chapels recorded in this study and concluded that only the assets registered in the book at the moment it is listed as heritage, it is not the guarantee of the cultural heritage preservation, the lack of effective management of the cultural heritage of from municipality aims at the action needs to ensure the preservation of the wooden chapels in the city of Maringá for the community memory